Natural Drugs From Plants 2022
DOI: 10.5772/intechopen.99242
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Aminobutyric Acid (GABA) and the Endocannabinoids: Understanding the Risks and Opportunities

Abstract: The Gamma-aminobutyric acid (GABA) system is the main inhibitory neurotransmitter system in the central nervous system (CNS) of vertebrates and is involved in critical cellular communication and brain function. The endocannabioid system (ECS) was only recenty discovered and quickly recognized to be abundantly expressed in GABA-rich areas of the brain. The strong relationship between the GABA system and ECS is supported both by studies of the neuraoanatomy of mammalian nervous systems and the chemical messaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“… 36 Examples include altering the levels and activities of the monoamine neurotransmitters dopamine, adrenaline, and serotonin; functioning as an N-methyl-D-aspartate receptor antagonist; activating the cannabinoid receptor type 1 (CB1); acting on the GABAA receptor to generate sedative, hypnotic, and anxiolytic effects; and interacting with opioid receptors and inhibitory neurotransmitters. 37 , 38…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Examples include altering the levels and activities of the monoamine neurotransmitters dopamine, adrenaline, and serotonin; functioning as an N-methyl-D-aspartate receptor antagonist; activating the cannabinoid receptor type 1 (CB1); acting on the GABAA receptor to generate sedative, hypnotic, and anxiolytic effects; and interacting with opioid receptors and inhibitory neurotransmitters. 37 , 38…”
Section: Resultsmentioning
confidence: 99%
“…36 Examples include altering the levels and activities of the monoamine neurotransmitters dopamine, adrenaline, and serotonin; functioning as an N-methyl-D-aspartate receptor antagonist; activating the cannabinoid receptor type 1 (CB1); acting on the GABAA receptor to generate sedative, hypnotic, and anxiolytic effects; and interacting with opioid receptors and inhibitory neurotransmitters. 37,38 Potential threats NPS are spreading at an incredible rate, endangering public health and complicating drug policy-making. 39 The negative health impacts and social harms of NPS are frequently poorly understood, which makes prevention and treatment extremely difficult.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…One of the possible mechanisms of the neuroprotective effects of CB1 receptor blockade is related to the receptor's role in the release of the neurotransmitter GABA. CB1 receptors have high expression on GABA neurons and these receptors' activity inhibits neurotransmitter release [71]. It has been found that upregulating GABA signaling aids in reducing injury in ischemic rat models; thus, blocking CB1 receptors should aid in producing this effect [72].…”
Section: Cb1 Receptor Antagonismmentioning
confidence: 99%